First known occurrence of the alpheid shrimps Leptalpheus forceps Williams, 1965 and L. marginalis Anker, 2011 (Decapoda: Caridea) in the state of Pará, Amazon region, Brazil - Rosário, Tayse N.; Pires, Marcus A.b.; Souza, Adelson S.; Fernandes, Marcus E.b.; Abrunhosa, Fernando A.; Simith, Darlan J.b. (Zootaxa, 2020)
In the present study, we report for the first time the occurrence of the alpheid shrimps Leptalpheus forceps Williams, 1965 and Leptalpheus marginalis Anker, 2011 in the state of Pará, in northern Brazil. Both Leptalpheus species (males, non-ovigerous females, and females carrying eggs) were collected from the burrows of the callichirid “ghost” shrimp, Lepidophthalmus siriboia Felder & Rodrigues, 1993, in a muddy-sandy intertidal zone of the Ajuruteua Peninsula, in the Bragança region. These records update the known geographical distribution of the two species, with L. forceps extending its Brazilian occurrence from the state of Bahia to state of Pará, and L. marginalis which was exclusively found on the Caribbean coast of Colombia is now recorded in Brazil.